Estudi microsintàctic del verb «caldre» en el català antic i en l’actual - Rigau, Gemma (Caplletra. Revista Internacional de Filologia, 2005)
The article offers a microsyntactic study about the clitics position in the sentences with impersonal existential verbs belonging to the class of caldre ‘to be necessary’. We contrast the behavior of this deontic verb in Old Catalan and in two present dialects: Ribagorçan Catalan and Central Catalan. It is shown that Ribagorçan dialect is parallel to Old Catalan: clitics related to the infinitive subordinated verb appear adjoined to caldre, in the main clause. This is the case of the clitic u (= «ho») in Old Catalan example «No u cal dir ara» (Roig, Spill, 7048) and its Ribagorçan equivalent: «No ho cal dir ara». However, in Central Catalan, there is not clitic climbing. Clitic objects of the infinitive verb have to remain in the subordinate clause: No cal dir-ho. This type of microcomparative analysis reveal itself as a proper way to establish a solid base for future studies on comparative syntax.